Genotype reaction of Solanum tuberosum, andigena and phureja groups to late blight (Phytophthora infestans Mont. De Bary) - Moncayo, Jennyfer; Delgado, Roberth; Marcillo, Carlos; Salazar, Claudia; Betancourth, Carlos (Revista de Ciencias Agrícolas, 2019)
Potato crop is the fourth main food product in the world, but is affected by Phytophthora infestans, the late blight disease causal agent. This research was carried out in a town of Pasto high plateau, South of Colombia. In order to evaluate the reaction of different genotypes of creole potato (Solanum tuberosum groups Phureja and Andigena) with regard the disease. A Randomized Complete Block design was established with three repetitions, where 30 genotypes were distributed and three plants were evaluated per repetition during two crop cycles in natural exposure to the pathogen. To assess the disease effect on production, the same genotypes were maintained with chemical control in an adjacent batch. Genotypes classified as tolerant are Chaucha Manzana, Cachuda, Criolla Colombia, Malvaseña, Andina and Criolla, during the first cycle with performance values ​​between 23 to 26t.ha-1 and during the second to Calavera Negra, Chaucha Paisa, Ratona, Criolla Galeras, Ratona Roja, Tornilla Roja and Aguacata with performance values ​​between 23 to 28t.ha-1. The graphic severity scale allowed genotypes to be categorized as susceptible and highly susceptible. The results indicate that for the prevalent pathogen race in this study area, there are no resistance sources within the studied collection. However, genotypes such as Criolla Colombia and Andina showed a better performance in terms of yield.